Challenges in RNA Regulation in Huntington's Disease: Insights from Computational Studies. Issue 7 (16th June 2020) - Palomino‐Hernandez, Oscar; Margreiter, Michael A.; Rossetti, Giulia
Abstract: Novel therapeutic approaches are being developed to tackle neurodegenerative diseases, due to the lack of efficiency of the known druggable targets. For Huntington's disease, a promising approach is the regulation of the RNA product. This target would allow for a selective and effective inhibition of the toxic effects exerted by the final nucleic product and the coded protein. In this review, the current state of the art of RNA regulation is discussed, with a brief but insightful view on novel plausible targets. After this, an emphasis on successful computational and experimental approaches tailored in modeling and regulating RNA aberrant behavior are extensively presented. Finally, the application and limitations of current computational methods are discussed, and possible avenues for improvement are outlined. Abstract :